Characterization of Human Mucosal‐associated Invariant T (MAIT) Cells. (20th September 2019) - Souter, Michael N.T.; Loh, Liyen; Li, Shihan; Meehan, Bronwyn S.; Gherardin, Nicholas A.; Godfrey, Dale I.; Rossjohn, Jamie; Fairlie, David P.; Kedzierska, Katherine; Pellicci, Daniel G.; Chen, Zhenjun; Kjer‐Nielsen, Lars; et al.
Abstract: Mucosal‐associated invariant T (MAIT) cells are a subset of unconventional T cells restricted by the major histocompatibility complex (MHC) class I–like molecule MHC‐related protein 1 (MR1). MAIT cells are found throughout the body, especially in human blood and liver. Unlike conventional T cells, which are stimulated by peptide antigens presented by MHC molecules, MAIT cells recognize metabolite antigens derived from an intermediate in the microbial biosynthesis of riboflavin. MAIT cells mediate protective immunity to infections by riboflavin‐producing microbes via the production of cytokines and cytotoxicity. The discovery of stimulating MAIT cell antigens allowed for the development of an analytical tool, the MR1 tetramer, that binds specifically to the MAIT T cell receptor (TCR) and is becoming the gold standard for identification of MAIT cells by flow cytometry. This article describes protocols to characterize the phenotype of human MAIT cells in blood and tissues by flow cytometry using fluorescently labeled human MR1 tetramers alongside antibodies specific for MAIT cell markers. © 2019 by John Wiley & Sons, Inc. The main protocols include: Basic Protocol 1 : Determining the frequency and steady‐state surface phenotype of human MAIT cells Basic Protocol 2 : Determining the activation phenotype of human MAIT cells in blood Basic Protocol 3 : Characterizing MAIT cell TCRs using TCR‐positive reporter cell lines Alternate protocols are provided for determining the absolute number, transcription factor phenotype, and TCR usage of human MAIT cells; and determining activation phenotype by staining for intracellular markers, measuring secreted cytokines, and measuring fluorescent dye dilution due to proliferation. Additional methods are provided for determining the capacity of MAIT cells to produce cytokine independently of antigen using plate‐bound or bead‐immobilized CD3/CD28 stimulation; and determining the MR1‐Ag dependence of MAIT cell activation using MR1‐blocking antibody or competitive inhibition. For TCR‐positive reporter cell lines, methods are also provided for evaluating the MAIT TCR‐mediated MR1‐Ag response, determining the capacity of the reporter lines to produce cytokine independently of antigen, determining the MR1‐Ag dependence of the reporter lines, and evaluating the MR1‐Ag response of the reporter lines using IL‐2 secretion. Support Protocols describe the preparation of PBMCs from human blood, the preparation of single‐cell suspensions from tissue, the isolation of MAIT cells by FACS and MACS, cloning MAIT TCRα and β chain genes and MR1 genes for transduction, generating stably and transiently transfected cells lines, generating a stable MR1 knockout antigen‐presenting cell line, and generating monocyte‐derived dendritic cells.